The Effect of Personal Competence, Emotional Stability, and Intrinsic Motivation on Teacher Work Commitment - Abdi, Wuri Tamtama; Wijaya, Candra; Ananda, Rusydi (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
The issue of work commitment is the basis of this study, examined through the lens of emotional stability, intrinsic motivation, and self-competence. The main purpose of this study is to explain the interaction between a person's emotional stability and their intrinsic motivation, as well as the teacher's competence towards the teacher's work commitment. This study uses a quantitative approach using ex post facto methodology. The research population was one hundred and ninety-one teachers from three different Madrasah Aliyah in Medan City. A questionnaire with a Likert scale was used to collect data. Using route analysis tools, research hypotheses are evaluated. The research results show: "(1) personal competence has a direct effect on intrinsic motivation by 36.20%, (2) emotional stability has a direct effect on intrinsic motivation by 34.70%, (3) personal competence has a direct effect on work commitment by 33, 90%, (4) emotional stability has a direct effect on work commitment of 37.20%, (5) intrinsic motivation has a direct effect on work commitment of 53.00%, (6) personal competence has an indirect effect on work commitment through intrinsic motivation of "81.40%, (7) emotional stability has an indirect effect on work commitment through intrinsic motivation of 79.70%, and (8) personal competence, emotional stability and intrinsic motivation simultaneously have an effect on work commitment of 78.00%."